Inhaled nitric oxide and arterial oxygen tension in patients with chronic obstructive pulmonary disease and severe pulmonary hypertension. Issue 2 (February 1997) - Katayama, Y; Higenbottam, T W; Diaz de Atauri, M J; Cremona, G; Akamine, S; Barbera, J A; Rodrìguez-Roisin, R
Abstract : BACKGROUND: Inhaled nitric oxide (NO) is a selective pulmonary vasodilator which can improve gas exchange in acute lung injury. However, it is uncertain that this effect on arterial oxygenation can be generalised to all lung diseases. METHODS: The effects of inhaled NO on gas exchange were studied in nine patients with chronic obstructive pulmonary disease (COPD), 11 patients with severe pulmonary hypertension, and 14 healthy volunteers. A randomized sequence of 40 ppm of NO or air was inhaled for 20 minutes through an orofacial mask. RESULTS: Inhaled NO reduced mean (SE) transcutaneous arterial oxygen tension (TcPO2) from 9.6 (0.3) to 8.9 (0.4) kPa in healthy volunteers and from 7.4 (0.6) to 7.0 (0.5) kPa in patients with COPD. There was no change in TcPO2 in patients with severe pulmonary hypertension. During inhalation of NO and air no change occurred in transcutaneous arterial carbon dioxide tension (TcPCO2), arterial oxygen saturation (SaO2) measured by pulse oximeter, or cardiac output determined by the transthoracic impedance method. CONCLUSIONS: Inhaled NO does not improve TcPO2 nor increase cardiac output in normal subjects and patients with COPD, suggesting that inhaled NO worsens gas exchange. This could represent inhaled NO overriding hypoxic pulmonary vasoconstriction in COPD. The finding that TcPO2 also fell when normal subjects inhaled NO suggests that a similar mechanism normally contributes to optimal gas exchange. Whilst inhaled NO can improve oxygenation, this effect should not be considered to be a general response but is dependent on the type of lung disease.